Triple funcionalidad del empresario; Socio, directivo y asalariado; Un enfoque administrativo y jurídico (National Administration Journal, 2021)
The paper addresses the business and legal figure referred to as the employer triple functionality, which is given by the existence of three specific and simultaneous conditions in the same person, being a shareholder, a member of the board of directors and being an employee at the same time and in the same company. The approach to this figure is based in an administrative and legal analysis, in which the legal and operational elements of each of the three conditions are analyzed, as well as the possible legal and technical discrepancies that may arise for the three defined positions, also an analysis of the existing regulations in the country is developed, as well as the government authorities interpretations of the issue. The paper ends with a regulation proposal that serves as a model to provide legal certainty to the employer in the country.
Keywords: Administration; Company; Entrepreneur; Shareholder; Board of Directors; Employee; Business Management; Corporative Law